2020
DOI: 10.3390/pathogens9090726
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Induces Mucin 19 Which Contributes to Viral Pathogenesis

Abstract: Human Metapneumovirus (HMPV) remains one of the most common viral infections causing acute respiratory tract infections, especially in young children, elderly, and immunocompromised populations. Clinical symptoms can range from mild respiratory symptoms to severe bronchiolitis and pneumonia. The production of mucus is a common feature during HMPV infection, but its contribution to HMPV-induced pathogenesis and immune response is largely unknown. Mucins are a major component of mucus and they could have an impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Previously, it has been observed that MUC19 downregulation alleviates lung viral infection diseases. 18 Here, it was indicated that MUC19 transcription levels increased after SP induction and decreased after METTL3 silencing but increased again after NEAT1 overexpression ( p < 0.05, Figure 5C). Based on this, it was hypothesized that the binding of NEAT1 to CTCF promotes the transcription of MUC19.…”
Section: Neat1 Binds To Ctcf and Promotes Muc19 Transcriptionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previously, it has been observed that MUC19 downregulation alleviates lung viral infection diseases. 18 Here, it was indicated that MUC19 transcription levels increased after SP induction and decreased after METTL3 silencing but increased again after NEAT1 overexpression ( p < 0.05, Figure 5C). Based on this, it was hypothesized that the binding of NEAT1 to CTCF promotes the transcription of MUC19.…”
Section: Neat1 Binds To Ctcf and Promotes Muc19 Transcriptionmentioning
confidence: 74%
“…It has been suggested that in human alveolar basal epithelial cells, HMPV can induce MUC19 production, 29 which is also involved in viral replication in the lungs of HMPV-infected mice. 18 Here, it was revealed that the SP induction elevated the MUC19 transcription levels, and MUC19 overexpression through intracellular transfection increased apoptosis and inflammatory factors in SP-induced AECs. Another study reported that overexpression of MUC19 can reduce oxidative stress and inflammation levels in AECs by inhibiting the TLR4/NF-κB signaling pathway.…”
Section: Muc19 Overexpression Attenuates the Protective Effect Of Met...mentioning
confidence: 84%
See 2 more Smart Citations
“…HMPV infection significantly increased expression of MUC1, MUC2, MUC4, MUC5AC, and MUC19 in both normal human bronchial epithelial cells and BALB/c mice ( 82 ). A recent study compared the differences in mucin expression between hMPV and RSV infections.…”
Section: Human Metapneumovirusmentioning
confidence: 99%